Continuity of the "Womb Writing" in Anaїs Nin's House of Incest (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This article explores the possibility of establishing a unique feminine aesthetics within the larger domain of female body politics in the French writer Anaїs Nin's controversial work, House Of Incest (1936). The article questions the apparent submerging of the female body in the literary representations of the canon. This research also attempts to study how Nin's formulation of the "womb writing" extends and, actually, precedes the tradition of l'ecriture feminine by way of analyzing the female body's engagement with and commitment to a continuous existence through the body's most basic organic function; i.e. (re)productivity.